Effectiveness of teaching mini handball through non-linear pedagogy in different socioeconomic contexts: A pilot study - Espoz Lazo, Sebastián.; Farías Valenzuela, Claudio Ítalo.; Reyes Contreras, Victor.; Ferrero Hernández, Paloma.; Giakoni Ramírez, Frano.; Tapia Zavala, Mauricio.; Duclos Bastías, Daniel.; Valdivia Moral, Pedro. (MDPI, 2022)
Mini handball is among the sports included as part of school physical education in Chile to improve children’s motor skills and to motivate their adherence to a healthy and active lifestyle in response to concerns about this country’s high level of childhood obesity. To this end, non-linear pedagogy (NLP) has been used to develop motor skills through mini handball in the school context. However, socioeconomic differences that influence the development of children’s motor skills have not been considered to determine whether the methodology applies to everyone. The aim of the present observational study is to describe and compare the effectiveness of the previously applied NLP methodology in two contrasting socioeconomic contexts to determine whether it helps to develop motor skills through mini handball in both school contexts. The Levine test was used to determine the homogeneity of the variances (p < 0.05), as the distribution of the data was not normal. The Kruskal–Wallis H statistical test was used to analyse within-group data. Additionally, the Mann–Whitney U test was applied for comparisons between groups. The results show significant improvements in the acquisition of the expected motor skills specific to mini handball. Additionally, a shortening of the gap was evidenced between the groups during the training process, with no significant differences at the end of the progression. Therefore, the investigated NLP is equally as effective for schoolchildren in two opposite socioeconomic contexts.
Keywords: Pre-sports; Sport pedagogy; Team sport; Aptitud motora; Eruditos